Adaptive high-performance and multifunctional façade systems - Matheou, Maria; Phocas, Marios C.; Christoforou, Eftychios G.; Müller, Andreas (Frontiers in Built Environment, 2026)
Adaptive, high-performance and multifunctional façades are recognized as key contributors to the EU’s climate-neutral agenda, as outlined in Directive (EU) 2024/1275, the Renovation Wave, and Horizon Europe initiatives. These systems provide environmental control (daylight, shading), serve as an interface between indoor and outdoor environments and minimize reliance on heating, cooling and artificial lighting systems, enhancing energy efficiency and occupant comfort. In addressing this challenge, this paper presents the design and prototyping of three adaptive façade typologies aiming to combine a multifunctional role of controlling, redirecting and/or harvesting solar radiation. Designed through a performance-driven, integrated design methodology, aspects of morphology (system composition, geometrical characteristics), materiality and embedded actuation are discussed along with daylighting and irradiance analyses. To analyze their potential for visual comfort (daylight quality, glare, view to the outside) and solar harvesting, simulation studies were conducted for four distinct climatic conditions, corresponding to each case study using Climatestudio and Ladybug plug-ins for Grasshopper/Rhino 3D. Each façade is evaluated in its climatic context and the outcomes are synthesized through a cross-case comparative framework that links climate driver, performance objective, and actuation-feasible states. The first façade system uses a retroreflector’s geometry to redirect solar radiation back toward its source, potentially reducing short-wave radiative loading near the façade by redirecting incident radiation toward the sky, while cable-driven actuation allows multiple folded states. The second system reinterprets static folding geometries, the so-called “Hortenkachel” into a kinetic shading system of translucent panels. The third prototype introduces rectangular photovoltaic modules supported by a cable net and strut framework facilitating solar tracking. All case examples are based on lightweight construction principles and mechanical simplicity in their kinematics. Prototypes complement the simulation studies and provide proof-of-concept validation for the kinematic behaviour of the adaptive high-performance façade systems. The novelty lies in (i) extending retroreflective optics into a kinetically reconfigurable façade for controlled solar-radiation redirection near the façade, and (ii) extracting transferable design principles across three typologies that refer to morphology, control logic, and multi-criteria performance (daylight, glare, view, radiation/energy). The reported façade states, performance ranges, and prototype strategies provide an archival benchmark for early-stage adaptive multifunctional façade design.